Turbidimetric Method: A Multi-Advantageous Option for Assessing the Potency of Ceftriaxone Sodium in Powder for Injection - da Trindade, Mariana Teixeira [UNESP]; Kogawa, Ana Carolina; Salgado, Hérida Regina Nunes [UNESP] (Oxford University Press (OUP), 2021)
BACKGROUND: Ceftriaxone sodium, an antimicrobial used in parenteral form, does not have a microbiological method by turbidimetry described in the literature. For drugs from antimicrobial class, the existence of a microbiological method for assessing their potency is essential. Not only are the results from the physical-chemical methods enough, but microbiological analyzes are also necessary. OBJECTIVE AND METHODS: Thus, this paper reports the development and validation of an efficient, accurate, reproducible, fast, and low-cost microbiological assay by turbidimetry to quantify ceftriaxone sodium in powder for injection. Water was used as the diluent to prepare the ceftriaxone solutions. BHI broth as used as culture media for the growth of the S. aureus ATCC 6538 at 9%. RESULTS: The method was linear in the range of 100-196 µg/mL, selective against the sample adjuvants and the forced degradation test, precise (intraday RSD 4.53%, interday RSD 3.85% and between analysts tcalculated 0.14 < 2.23 tcritical), accurate with recovery of 100.33% and robust against minor changes in the volume of culture medium used, wavelength, incubation time, and inoculum concentration. CONCLUSIONS AND HIGHLIGHTS: The turbidimetric method developed in this paper is a convenient and valuable alternative to the routine quality control of ceftriaxone sodium in powder for injection, since it allows a reliable quantification and can be used to complement the physical-chemical analysis.